The Effectiveness of Administrative Training Courses and Their Relationship to Classroom Management Among Physical Education Teachers in the Samarra Directorate of Education - Mohammed Rashid Mohammed; Hussein Tareq Hussein; Mahmood Munshid Murshed (International Journal of Experimental Sports Science Research, 2026)
Backgroud: This study was aimed at examining the impact of administrative training courses and its relationships with classroom management of physical education teachers at the Samarra Education Department. This research is based on the assumption that the administrative training can be considered the essential component in developing professional competences of the teacher and keeping up with the educational and pedagogical developments in school sports. The classroom management can be viewed as the key competence in achieving the goals of the educational process. Methods: A descriptive research methodology was used with the use of a survey-analytical approach and correlational analysis, which was recognized as the most suitable approach to research problem and its goals. The research population consisted of 134 physical education teachers of the Salah Al-Din Directorate of Education, Samarra Education Department. The participants were divided into the pilot sample of 10 teachers and the main sample of 124 teachers. The questionnaire was used as the main research instrument, which comprised the Administrative Training Scale of five factors and 15 questions, as well as the Classroom Management Scale. Results: It was found that there is a statistically significant positive correlation between the effectiveness of administrative training courses and classroom management (p = 0.017). Moreover, it was revealed that the physical education teachers have satisfactory participation in administrative training courses and possess sufficient skills of classroom management. Conclusions: Administrative training plays the important role in the formation of professional attitude and motivates to work. Moreover, it makes the transition from the routine professional activity to the modern developments in school sports possible